FORMS OF LEARNING SUPPORT PROVIDED BY IMPLEMENTING ON-GOING ASSESSMENT IN AN EYL CLASS - Amy Kustina (Journal of English and Education, 2014)
This paper reports the presence of learning support provided by on-going assessment in an EYL class. This study involved 31 of third grade students in an elementary school in Bandung. Moreover, this study employed Classroom Action Research and conducted observation and document analysis in the process of collecting the data. The results showed that on-going assessment provided learning supports in the forms of the use of models of language use, building students’ motivation (intrinsically and extrinsically) and building student’ autonomy and responsibility for their further learning. In this case, selecting varied materials and forms of assessments that suit to young learners was the main aspects to consider in implementing on-going assessment in an EYL class. Keywords: on-going assessment, English for Young Learners (EYL)